Detection of counterfeit Durateston using Fourier transform infrared spectroscopy and partial least squares : discriminant analysis - Neves, Diana Brito da Justa (2017)
Medicines containing anabolic steroids are one of the main targets for counterfeiting worldwide, including Brazil. The aim of this work was to propose a method for discriminating original and counterfeit Durateston® ampoules by Fourier transform infrared spectroscopy (FTIR) followed by chemometric analysis. Ninety-six ampoules of Durateston®, 49 originals and 47 counterfeits, were analyzed by gas chromatography with mass spectrometry (GC-MS) and by FTIR. Principal component analysis was applied to the infrared spectra to detected different clusters, corresponding to original samples and different types of counterfeits. A partial least squares - discriminant analysis method was proposed to discriminate original samples from those counterfeits that were indistinguishable from the originals in the infrared analysis. A training subset comprised of one-third of the available spectra was used to establish a suitable model that correctly discriminated all samples in the test subset, resulting in 0% of false positive or negative results and 100% of efficiency rate, sensitivity and specificity. In addition to the low cost of the infrared technique, the proposed method is fast, reliable and suitable to replace GC-MS methods used in Durateston® ampoule analyses to detect counterfeiting.